1998
DOI: 10.1021/la980320k
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Measuring the Effect of a Monolayer on Molecular Transfer across an Air/Water Interface Using Scanning Electrochemical Microscopy

Abstract: A new approach is described for the quantitative study of the effect of a monolayer on solute transfer rates across an air/water interface. The technique is illustrated through measurements of oxygen transfer across a monolayer of 1-octadecanol as a function of compression. The experimental approach uses an inverted ultramicroelectrode (UME), positioned in the water phase in a Langmuir trough close to the air/water interface to induce the transfer of oxygen from air to water via the reduction (and depletion) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(132 citation statements)
references
References 34 publications
7
124
0
1
Order By: Relevance
“…On the other hand, a current increase is recorded when approaching the air/liquid interface with the probe biased to −0.8 V vs. Ag QRE. This is due to the fast transfer of oxygen from air into the solution to replace the oxygen depleted at the probe tip [71]. Notice that the air/liquid interface can be deformed during the approach curve due to the presence of the micrometer probe in its vicinity, and even drag a small portion of liquid into the other phase [72].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a current increase is recorded when approaching the air/liquid interface with the probe biased to −0.8 V vs. Ag QRE. This is due to the fast transfer of oxygen from air into the solution to replace the oxygen depleted at the probe tip [71]. Notice that the air/liquid interface can be deformed during the approach curve due to the presence of the micrometer probe in its vicinity, and even drag a small portion of liquid into the other phase [72].…”
Section: Resultsmentioning
confidence: 99%
“…44,45 For the ORR, the flux of oxygen is provided by diffusion down the barrels of the pipette into the electrolyte meniscus as well as across the air-water interface of the meniscus ( Figure 1A), which is a rapid process. 46 Consequently, the diffusion-limited current 30 (approximately 40 -45 pA as marked by dashed line in Figure 1C) is much higher than would be expected if diffusion was only due to O 2 initially in solution (ca. 27 pA based on meniscus height of 150 nm, see ESI, section 2).…”
mentioning
confidence: 82%
“…Indeed, previous investigations have found that the electron transfer between ferrocene and hexacyanoferrate(III) at the liquid/liquid interface occurs by the same route, partitioning of ferrocene to water and reaction with hexacyanoferrate(III) homogeneously on the aqueous side of the interface [38]. Considering that oxygen is more soluble in DCE than in water, oxygen reduction by DMFc on the aqueous side of the interface is likely to be accompanied by oxygen transfer at the water/DCE interface and by transfer from the surrounding air atmosphere [39,40]. Considering Scheme 4, the current offset is the steady state diffusion current due to DMFc + transfer back from water, following the partition of DMFc from the organic phase and H 2 O 2 production on the aqueous phase of the interface.…”
Section: Dmfc Partition and Signal IImentioning
confidence: 99%